Exploring views on caregiving for older persons among formal social care workers in Malaysia: a qualitative study - Minhat, Halimatus Sakdiah; Mat Din, Hazwan (Taylor and Francis, 2020)
The rapid ageing process experienced by many developing countries, lead issues and challenges to deal with the highly demanding social care sector. This qualitative study aimed to explore the understanding and views of the formal caregivers in Malaysia towards social care for older persons. Series of focus group discussions were conducted among 57 institutional social care workers at four public residential care in Peninsular Malaysia based on the identified zones. Two groups of participants involved, those aged less than 40 years old and 40 years old and above, divided based on the mean age. The interview was transcribed verbatim and inductive thematic analysis was conducted to identify the related coding and themes. Three themes were identified to explain the views and understanding of the participants related to social care for older persons namely, religious values, health impact and knowledge. Although many participants emphasized on the negative impact of caregiving for older persons on physical and mental health of the caregivers, they also viewed the job as noble and a useful platform to gain knowledge and enrich their personal experiences related to the later life. Acknowledgement of the negative impacts on health of the carers by the relevant authorities are very important to ensure productivity and quality of work, healthy and safe workplace environment and maintaining the rights of workers.